2003
DOI: 10.1111/j.1756-1051.2003.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal flowers in genus Alpinia

Abstract: There are six types of abnormal flowers in Alpinia described in this paper, namely 2‐stamens, 1.5‐stamen, 1‐stamen, stamen with only one theca, stamen absent and twin‐flower. A different morphological nature of subulate appendage is proposed: it might be the androecial appendage, i.e. appendage of stamen or labellum, but not of staminode. The second type of the abnormal flowers with 1.5‐stamen is regarded as synapomorphy, which is absent in the extant taxa, of the four ginger families, from which were derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…Apart from about 2 two-staminate flowers, we observed another two types of abnormal flowers with one fertile stamen in A. intermedia, 1 to 2 flowers with two labella and 1 to 2 flowers with three appendages. Song et al [59] reported that the number of fertile stamen, labellum, appendage, and petal varied in different species of Alpinia genus flowers, and the relative position of fertile stamen, labellum, appendage, and petal was different from normal flowers, rotated from adaxial plane to lateral to abaxial. The continuous variation in the number of stamen may be the reappearance of the evolutionary history of the stamen in the ginger group and even in Zingiberales [59].…”
Section: Labellum-androecial Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from about 2 two-staminate flowers, we observed another two types of abnormal flowers with one fertile stamen in A. intermedia, 1 to 2 flowers with two labella and 1 to 2 flowers with three appendages. Song et al [59] reported that the number of fertile stamen, labellum, appendage, and petal varied in different species of Alpinia genus flowers, and the relative position of fertile stamen, labellum, appendage, and petal was different from normal flowers, rotated from adaxial plane to lateral to abaxial. The continuous variation in the number of stamen may be the reappearance of the evolutionary history of the stamen in the ginger group and even in Zingiberales [59].…”
Section: Labellum-androecial Identitymentioning
confidence: 99%
“…Song et al [59] reported that the number of fertile stamen, labellum, appendage, and petal varied in different species of Alpinia genus flowers, and the relative position of fertile stamen, labellum, appendage, and petal was different from normal flowers, rotated from adaxial plane to lateral to abaxial. The continuous variation in the number of stamen may be the reappearance of the evolutionary history of the stamen in the ginger group and even in Zingiberales [59]. The number of fertile stamen from 2, 1.5, 1, 0.5 to 0, varies continuously to some extent, with intermediate phenotypes of one stamen being the most common.…”
Section: Labellum-androecial Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…From the above how many staminodes composing labellum largely depends on the staminode development. In the abnormal flowers of Alpinia genus, a tendency for the number of fertile stamens varied from 2, 1 to 0.5 may be the reappearance of the evolutionary history of the stamen in the ginger group and even in Zingiberales (Song et al, 2003). Nevertheless, so far no fossil evidence has indicated that the number of stamen evolves between 6/5 and 1.…”
Section: Discussionmentioning
confidence: 98%
“…Maas (Maas, 1977) found an abnormal flower of Renealmia goyazensis, in which the lateral appendages of the labellum were replaced by two fully developed anthers. Song (Song et al, 2003) reported a considerable diversity of developmental switches in the genus Alpinia. Analyses of the abnormal flowers allow us to deduce robust rules of homeotic transformation that could potentially be generalized across the Zingiberaceae.…”
Section: Introductionmentioning
confidence: 99%